(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 1991)
In the central-eastern areas of the Trento Platform (Asiago Plateau, Lavarone Plateau, Valsugana and Mt. Grappa) many stratigraphic sections at lower-middle Jurassic boundary have been examinated. The aim of the research was to describe the Toarcian-Aalenian sediments or their gaps in these platform areas. The crinoidal cross-bedded calcarenites (San Vigilio Oolite) whose thickness is 70 m, situated at Mt. Agaro and at Mt. Grappa, have been attributed to Aalenian. The oolitic calcarenites (Grigno Member- Calcari Grigi) which show their maximum thickness at Mt. Agaro and at Grigno have been doubtfully attributed to Toarcian.